Madeira de Pinus patula e de Pinus taeda para laminação e produção de painéis multilaminados - Tavares, Everton Lorenzett (2017)
Timber of Pinus sp. was established in the Brazil by fiscal incentives, being the main source of raw material in the plywood industry in the South of country. Due to problems with monkey attack in Pinus taeda plantations, Pinus patula Schltdl & Cham has been gaining prominence due to the fact this species is not attacked by these animals. Some companies were interested in establishing plantations with this last species, but have doubts about the timber quality. Thus, the study had as objectives to evaluate the effects of the species, the tree diameter class and the log longitudinal position in the timber basic density; Comparing the venners yield of this species with that of Pinus taeda and evaluating the quality of plywood / LVL panels produced with Pinus patula and Pinus taeda wood veneers bonded with ureaformaldehyde resin, intended for internal use, and phenol-formaldehyde, intended for external use. An experiment was carried out to evaluate the effects of the timber species and the venners composition in balanced construction on the panel properties(density, moisture content, thickness, water absorption, thickness swelling, static bending, parallel and perpendicular to the grain, and bonded quality). Twelveyear-old trees planted in the municipality of Bituruna-PR were separated into three classes of DBH (17 to 22.99, 23 to 32.99 and ≥ 33 cm). Pinus patula wood presented lower basic density and higher venners yield than Pinus taeda. The panels produced with Pinus patula wood presented properties that met the quality standards required by ABIMCI, with the exception of the apparent density. The analysis of the balanced construction effect confirmed that the venner thickness is the one that most influences the balance of the panels propertiesand that the dimensional stability, stiffness and resistance of the compensated panel can be estimated as a function of the thickness of venners positions, parallel and perpendicular, panel direction.